Cold-Active Shewanella glacialimarina TZS-4T nov. Features a Temperature-Dependent Fatty Acid Profile and Putative Sialic Acid Metabolism - Qasim, Muhammad Suleman; Lampi, Mirka; Heinonen, Minna-Maria K.; Garrido-Zabala, Berta; Bamford, Dennis H.; Käkelä, Reijo; Roine, Elina; Sarin, Leif Peter (Frontiers in Microbiology, 2021)
Species of genus Shewanella are among the most frequently identified psychrotrophic bacteria. Here, we have studied the cellular properties, growth dynamics, and stress conditions of cold-active Shewanella strain #4, which was previously isolated from Baltic Sea ice. The cells are rod-shaped of ~2 µm in length and 0.5 µm in diameter, and they grow between 0–25°C, with an optimum at 15°C. The bacterium grows at a wide range of conditions, incl. 0.5–5.5% w/v NaCl (optimum 0.5–2% w/v NaCl), pH 5.5–10 (optimum pH 7.0) and up to 1 mM hydrogen peroxide. In keeping with its adaptation to cold habitats, some polyunsaturated fatty acids, such as stearidonic acid (18:4n-3), eicosatetraenoic acid (20:4n-3), and eicosapentaenoic acid (20:5n-3), are produced at a higher level at low temperature. The genome is 4456 kb in size and has a GC content of 41.12%. Uniquely, strain #4 possesses genes for sialic acid metabolism and utilizes N-acetyl neuraminic acid as a carbon source. Interestingly, it also encodes for cytochrome c3 genes, which are known to facilitate environmental adaptation, incl. elevated temperatures and exposure to UV-radiation. Phylogenetic analysis based on a consensus sequence of the seven 16S rRNA genes indicated that strain #4 belongs to genus Shewanella, closely associating to Shewanella aestuarii with a ~97% similarity, but with a low DNA-DNA hybridization (DDH) level of ~21%. However, average nucleotide identity (ANI) analysis defines strain #4 as a separate Shewanella species (ANI score = 76). Further phylogenetic analysis based on the 92 most conserved genes places Shewanella strain #4 into a distinct phylogenetic clade with other cold-active marine Shewanella species. Considering the phylogenetic, phenotypic, and molecular characterization, we conclude that Shewanella strain #4 is a novel species and name it Shewanella glacialimarina sp. nov TZS-4T, where glacialimarina means sea ice. Consequently, S. glacialimarina TZS-4T constitutes a promising model for studying transcriptional and translational regulation of cold-active metabolism.